Penerapan Pembelajaran Ekstrakulikuler Tari untuk Penanaman Karakter bagi Siswa Sekolah Dasar - Shilla Febriyani; Ibnu Muthi (Pusat Riset dan Inovasi Nasional, 2024)
The learning model is a fusion of dance integrated approach to free expression, discipline and multicultural. The problem is how to form and execution of an integrated model of learning the art of dance in elementary school students. The purpose of this study was to determine and implement an integrated model of learning in elementary school students. This study uses the approach of Research and Development (R & D), engineering data collection through observation, interviews, and documentation, as well as the validity of the data using triangulation of data analysis process includes three grooves activities as a system, namely data reduction, data presentation, and conclusion. The results showed that the integrated model of learning dance implemented through three stages: (1) disciplinary approaches, (2) using a multicultural approach that includes process flow that is penengenalan appreciation, understanding, appreciation and evaluation, (3) approach in which free expression using creation method which ideas and concepts, plugging into a new motion products. Advice, elementary school teachers should use the integrated arts learning model that students have the experience to appreciate and be creative.